INFLUENCE OF PLANT SPACING AND WEED CONTROL PRACTICES ON THE GROWTH AND YIELD OF OKRA (Abelmoschus esculentus (L) Moench) IN BADEGGI - Ndagana, M.K.; Aliyu, J.A.; Ahmad, B.S. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
Field study was conducted at the National Agricultural Extension Research and Liaison Service (NAERLS)/ABU Sub-station Badeggi, Niger State, Nigeria during 2024 cropping season to assess growth and yield of Okra (Abelmoschus esculentus (L) moench) in response to plant spacing and weed control. The treatments consisted of three (3) plant spacing (60 cm x 50 cm, 60 cm x 40 cm and 60 cm x 30 cm) and three (3) mulching practices (Dry grass mulch, Black polyethylene mulch, Sawdust mulch) and two (2) hoe weeding (at 3 and 7 Weeks after Sowing (WAS) and weed free plots were used as control. These were factorially arranged and laid out in a randomized complete block design with three replications. The mulching materials were applied before sowing seeds. A split application of NPK 15:15:15 was done at 2 and 6 WAS at the rate of 200 kg/ha by side placement. Analysis of Variance (ANOVA) for the data was carried out using GenStat 3 release 2005. Significant differences between means were estimated by the Least Significant Difference (LSD) at 5% level of significant. Result revealed that plant spacing were not significant in most of the parameters assessed. Plots mulched with black polyethylene mulch significantly (P<0.05) performed better than other weed control treatments in terms of lower number of weeds (0.92/0.5m2), lower weed biomass (2.67g/0.5m2), higher crop pod yields (0.39tons/ha) and higher plant height (63.33cm). Plant spacing and mulching with black polyethylene within the confines of the study was therefore recommended for higher Pod yield of Okra.